Imaginario social sobre el medio comunitario tvmicc canal 47 en Latacunga. - Naranjo Silva, Esthela Silvana (2013)
This research project focuses on analyzing the social imaginary which exist in the indigenous sector and farmer in Latacunga about TVMICC channel 47 (Television of the indigenous movement and farmer from Cotopaxi), the first community channel of Ecuador. A revision of ideas was done from various authors about the community communication, community media, social imaginaries, TVMICC, among other concepts that are the main points of research of this project. In this research was conducted interviews to indigenous leaders and farmers of Cotopaxi, social communicators and staff of TVMICC. In addition, 262 surveys were applied to the audience of the channel in the parishes San Buenaventura and Belisario Quevedo of Latacunga Canton in Cotopaxi province. In what corresponds to the results, the principal social discourses are exposed that allow to know since your optics the social imaginaries were formed that exist on the community channel, the same are also described later. This work constitutes a tool for future research about community media of Ecuador. Likewise, of this project comes off the approach to the current reality of TVMICC and alternatives to reduce the weaknesses that presents the community media analyzed, which are reflected in the final conclusions and recommendations, respectively.